Iron intake and anemia as predictors of preeclampsia risk in pregnant women in the second trimester - Salmah Arafah; Dewiyanti Dewiyanti; Ernawati Ernawati; Dina Oktaviana; Kamriana Kamriana; Alwi Alwi; Zainuddin Zainuddin; Nur Hijrah Syaharani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Preeclampsia remains one of the leading causes of maternal morbidity and mortality worldwide, including in Indonesia. Iron deficiency anemia is considered a modifiable risk factor; however, few studies have specifically examined the relationship between anemia status and iron intake and the risk of preeclampsia during the second trimester of pregnancy. This study aimed to analyze the relationship between anemia status and iron intake and the risk of preeclampsia among second-trimester pregnant women. A cross-sectional analytical design was employed involving 150 pregnant women selected through purposive sampling in the working area of Pattallassang Public Health Center, Takalar Regency, between January and March 2025. Data were collected through hemoglobin level examination, a Food Frequency Questionnaire (FFQ) for iron intake assessment, and medical records for preeclampsia diagnosis. Data were analyzed using chi-square and logistic regression tests to determine the associations and predictive strength. The results showed that 30% of respondents experienced preeclampsia, 42% had anemia, and 64% had an inadequate iron intake. Anemia and inadequate iron intake were significantly associated with an increased risk of preeclampsia (p < 0.05). In conclusion, anemia and iron intake are important predictors of preeclampsia risk, highlighting the need for nutritional screening and early intervention to prevent further complications.